2020
DOI: 10.1002/adhm.202001034
|View full text |Cite
|
Sign up to set email alerts
|

Let's Talk About Sex—Biological Sex Is Underreported in Biomaterial Studies

Abstract: Precision medicine aims to better individualize healthcare. It requires that biomaterials be designed for the physiological characteristics of a specific patient. To make this a reality, biomaterials research and development must address differences of biological sex. More specifically, biomaterials should be designed with properties optimized and appropriate for male and female patients. In analyzing research articles from seven prominent biomaterials journals, sex as a biological variable is missing from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 122 publications
(122 reference statements)
0
21
1
Order By: Relevance
“…For every journal article found, we recorded the body tissue the cells were derived from, whether the cells were from an immortalized cell line, the ancestry identified either specifically stated in the paper or inferred from outside sources such as public databases or cell suppliers, and the sex of the cells. Our research involving the race/ancestry of the cells found a lack of representation in literature which holds to the finding of previous work [11,12].…”
Section: Race/ancestry Is Underreported In In Vitro Biomaterial-based Studiescontrasting
confidence: 58%
“…For every journal article found, we recorded the body tissue the cells were derived from, whether the cells were from an immortalized cell line, the ancestry identified either specifically stated in the paper or inferred from outside sources such as public databases or cell suppliers, and the sex of the cells. Our research involving the race/ancestry of the cells found a lack of representation in literature which holds to the finding of previous work [11,12].…”
Section: Race/ancestry Is Underreported In In Vitro Biomaterial-based Studiescontrasting
confidence: 58%
“…It is necessary to make this validation as this information may not be provided or be accurate from the vendor. [25] PCR was used to amplify in a single reaction a region of the sex-determining region Y (SRY) gene, specifically the region for testis-determining factor (TDF) (males only), and a region of the HLA-DQ gene, an internal control found on chromosome 6 (both males and females). [54] (The protocol uses two primer sets (Table 2) to amplify in a single reaction a region of the SRY gene, specifically the region for TDF (males only), and a region of the HLA-DQ gene, an internal control found on chromosome 6 (both males and females)).…”
Section: Sex Validationmentioning
confidence: 99%
“…Therefore, work involving human subjects requires a more rigorous safety and efficacy assessment of the NMs. Moreover, the development, progression mechanisms, and extent of many neurological diseases, especially neurodegenerative diseases, are closely related to the biological sex, age, and ancestral background of the disease models used for research, which is often neglected in biomaterials research [ 171 , 172 ], especially NM studies focused on redox stress-related neurological diseases. These factors should be carefully considered, as they may play a crucial role in neurological diseases for the reasons discussed as follow: First, there is sex.…”
Section: Perspectivesmentioning
confidence: 99%